Competition Intensity and Innovativeness in MSMEs: The Mediating Effect of Entrepreneurial-Based Intuitive Decision Making - Afandi, Eka Prasetia; Herdinata, Christian; Soelistyo, Brandon Orlando (Jurnal Aplikasi Manajemen, 2025)
Empirical evidence explaining how MSMEs transform intense competitive pressures into sustainable innovation through internal strategic mechanisms remains limited, especially in developing countries like Indonesia. Addressing this gap is urgent to identify adaptive decision-making processes that enable MSMEs to remain innovative and resilient in a highly competitive, resource-constrained environment. This study aims to analyze the effect of business competition intensity on innovativeness and entrepreneurial-based intuitive decision making, as well as the impact of such decision making on innovativeness. This study method used purposive sampling and involved 413 MSME actors in East Java as respondents. The data were processed using descriptive analysis and Structural Equation Modeling (SEM) through the AMOS program (Analysis of Moment Structure). The results show that the intensity of business competition has a significant positive effect on both innovativeness and intuitive entrepreneurial decision-making. In addition, intuitive entrepreneurial decision-making also has a significant positive effect on innovativeness. The main novelty of this study is the finding that entrepreneurial-based intuitive decision making can act as a strong mediator in the relationship between business competition intensity and innovativeness. The implications of the study underscore the importance of synergy between entrepreneurial attitudes and intuition to improve decision quality and encourage corporate innovation, especially in a highly competitive environment.